2022
DOI: 10.1038/s41598-022-07096-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatty acid metabolites on nocturia

Abstract: Dysregulation of circadian rhythm can cause nocturia. Levels of fatty acid metabolites, such as palmitoylethanolamide (PEA), 9-hydroxy-10E,12Z-octadecadienoic acid (9-HODE), and 4-hydroxy-5E,7Z,10Z,13Z,16Z,19Z-docosahexaenoic acid (4-HDoHE), are higher in the serum of patients with nocturia; however, the reason remains unknown. Here, we investigated the circadian rhythm of fatty acid metabolites and their effect on voiding in mice. WT and Clock mutant (ClockΔ19/Δ19) mice, a model for nocturia with circadian rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Increased fatty acid metabolites were also identified in the results of studies that looked for serum metabolomic biomarkers of nocturia [23,25]. This discovery led to preclinical research evaluating the circadian rhythm of fatty acid metabolism and their effect on voiding in mice [49], which showed that increased serum levels of fatty acid metabolites during sleep from circadian rhythm disturbances can cause nocturia and that fatty acid metabolic pathways were involved in the regulation of clock genes. Based on circadian rhythm disorders and recent findings on chronotherapy [50], these results may have two future dimensions, the first pathophysiological hypothesis of the involvement of fatty acid metabolites in nocturia and the second clinical with a possibility of monitoring circadian rhythm via metabolomic markers of fatty acids in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Increased fatty acid metabolites were also identified in the results of studies that looked for serum metabolomic biomarkers of nocturia [23,25]. This discovery led to preclinical research evaluating the circadian rhythm of fatty acid metabolism and their effect on voiding in mice [49], which showed that increased serum levels of fatty acid metabolites during sleep from circadian rhythm disturbances can cause nocturia and that fatty acid metabolic pathways were involved in the regulation of clock genes. Based on circadian rhythm disorders and recent findings on chronotherapy [50], these results may have two future dimensions, the first pathophysiological hypothesis of the involvement of fatty acid metabolites in nocturia and the second clinical with a possibility of monitoring circadian rhythm via metabolomic markers of fatty acids in serum.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between ω-3 fatty acids and the molecular clock should not only be understood as exerted by the former on the latter but as a bidirectional relationship. In murine models, urinary levels of fatty acid metabolites, such as 4-hydroxy-5E, 7Z, 10Z, 13Z, 16Z, and 19Z-docosahexaenoic acid (4-HDoHE), were higher in CLOCK mutant compared with wild-type mice [ 160 ]. From a neurological point of view, RORα deficiency was associated with alterations in fatty acid accretions in the cerebellum and secondary neurological impairments [ 161 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 0.4% of adults under the age of 40 have nocturia, compared to 11.5% of those over the age of 60 [29]. Additionally, men with normotension were 39% less likely than untreated hypertensive patients to report nocturia [30].Therefore, risk factors for nocturia include aging, hypertension, diabetes, and obesity [27,28,31,32], which all contribute to chronic renal disease [33][34][35][36]. However, we conducted an interaction study of variables with nocturia to validate their impact on the result, and it revealed that hypertension alone substantially impacted the association between nocturia and eGFR.…”
Section: Discussionmentioning
confidence: 99%